Teens in Turkey - Alexandra Lilly (Minneapolis, MN, United States COMPASS POINT BOOKS, 2008)
Turkish teenagers are living in country that combines ancient civilizations with shopping malls, cell phones, and other aspects of modern life. The country, like much of the world, is trying to balance traditional religion and culture with lifestyle changes that come with being a progressive nation. Teens are at the forefront of this challenge, leading the way. Teens in Turkey is part of Global Connections, a series that uncovers the challenges, pastimes, and customs of teens around the world.
Keywords: Non Fiction